BEBERAPA FAKTOR YANG BERHUBUNGAN DENGAN MOTIVASI WIRAUSAHA WARUNG JAMU DI JAKARTA - imam Imron (Media Riset Bisnis & Manajemen, 2004)
Medical herb stall was bom from entrepreneurs who have different living backgrounds so that their motivation to do business of medicinal herb stall is also different. Their motivation to do businesds of medicinal herb stall,among other things,is the motivtion to meet basic needs,motivation of growth expectation and motivation of enforcement over their success of failure in the past. The objective of this research is to identify factors that relate to entrepreneurial motivation of medicinal herb stall. This research is conducted only in entrepreneur of medicinal herb stall- an informal sector that has permanent businesds place and open al the times both day and night with the location in Jakarta Barat area. Hypothesis (ha) has a relationship between business motivation of entrepreneur of medicinal herb stall. Research method is employing descriptive research. To collect the primary data, aquestionare is used with the sample of 100 people. From the research results,it is suggested that there is aposotove relation between motivation and entrepreneur of medicinalherb stall in Jakarta Barat, that the existence of medicinal herb stall is infuenced by the motivation of an entrepreneurto meet basicneeds of 39 % and motivation of enforcement over their succes or failure in the past ranks finalposition of only 26 %.